2022
DOI: 10.3390/ph15121589
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrion-Targeted NIR Therapeutic Agent Suppresses Melanoma by Inducing Apoptosis and Cell Cycle Arrest via E2F/Cyclin/CDK Pathway

Abstract: Malignant melanoma is the most fatal form of skin cancer worldwide, and earlier diagnosis and more effective therapies are required to improve prognosis. As a possible solution, near-infrared fluorescent heptamethine cyanine dyes have been shown to be useful for tumor diagnosis and treatment. Here, we synthesized a novel theranostic agent, IR-817, a multifunctional bioactive small-molecule that has near-infrared emission, targets mitochondria in cancer cells, and has selective anti-cancer effects. In in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…As shown in Figure 5A, even at a high concentration (80 μM), the cell viability was ~60%, whereas previous studies confirmed that the cell viability of A375 and B16-F10 after 24 h of treatment with 10 μM IR-817 was ~10%. 26 This indicated that BSA@IR-817 could reduce the toxicity of IR-817 significantly. Subsequently, BSA@IR-817 was validated as a photothermal agent for the laser-induced ablation of cancer cells.…”
Section: Photoinduced Cytotoxicity Of Bsa@ir-817 In Melanoma Cellsmentioning
confidence: 93%
See 3 more Smart Citations
“…As shown in Figure 5A, even at a high concentration (80 μM), the cell viability was ~60%, whereas previous studies confirmed that the cell viability of A375 and B16-F10 after 24 h of treatment with 10 μM IR-817 was ~10%. 26 This indicated that BSA@IR-817 could reduce the toxicity of IR-817 significantly. Subsequently, BSA@IR-817 was validated as a photothermal agent for the laser-induced ablation of cancer cells.…”
Section: Photoinduced Cytotoxicity Of Bsa@ir-817 In Melanoma Cellsmentioning
confidence: 93%
“…Near-infrared dye IR-817 was synthesized following our previously reported protocol. 26 Antibodies against Ki-67 was purchased from Cell Signaling Technology (CST, Beverly, MA, USA). Antibodies against Cleaved caspase-3 (CC-3) was purchased from Zen-bio (Chengdu, China).…”
Section: Materials and Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 2 (1.42 g, 4 mmol), 9-Anthraldehyde (0.824 g, 4 mmol) and CH 3 COONa (0.328 g, 4 mmol) were dissolved in EtOH (20 mL), and stirred at 70 C for 2 h, then the dark red solution was obtained. 25 Then, the solvent was removed by vacuum evaporation, and CH 2 Cl 2 / CH 3 OH (10/1, v/v) was used as eluent for silica gel column purification to obtain dark red solid products. The IUPAC name: (E)-2-(2-(anthracen-9-yl)vinyl)-1-(5-carboxypentyl)-3,3-dimethyl-3Hindol-1-ium bromide.…”
Section: Scz0148mentioning
confidence: 99%